An important step towards an understanding of the type of the philosophy at the Center of Interdisciplinary Studies - Janusz, Robert (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
The Center of Interdisciplinary Studies in Cracow has a very rich tradition that has been studied by many and recently by Kamil Trombik. The very difficult period for the Church and for philosophy during the materialistic Marxist ideology was an opportunity for card. K. Wojtyła to outline a new mode of dialog between science and religion. The future Center, organized by Michał Heller and Józef Życiński not only captured this idea but transformed it into an academic institution centered on the idea of philosophy in science, which was also developed at the Vatican Observatory by W.G. Stoeger et al. Trombik’s book is an excellent study of the historical context and initial years of activity of the Center and its development.